Diagnostic and therapeutic challenges in managing purulent pericardial effusion with concurrent pneumonia: A geriatric case report - Vori, Ira; Anjarwani, Setyasih; Tjahjono, Cholid Tri (Heart Science Journal, 2025)
Introduction: Purulent pericarditis is defined as an infection in the pericardial space that produces macroscopically or microscopically purulent fluid. It was a rare but life-threatening condition. It may be primary or secondary to another infectious process. This condition, characterised by an infectious or inflammatory accumulation of fluid in the pericardial cavity, presents significant diagnostic and therapeutic challenges, particularly in the context of multiple comorbidities. The purpose of this case report is to provide descriptive information about rare clinical patient scenario of purulent massive pericardial effusion in elderly. Case Description: The patient's presentation, complicated by pneumonia and diabetes mellitus, underscores the complexities in diagnosing and managing an 85-year-old male patient with diverse medical backgrounds. Echocardiography confirmed the diagnosis of massive pericardial effusion and showed the purulent fluid from the pericardiocentesis procedure. Nevertheless, despite various efforts to find the origin of the infection and treat it with antibiotics according to the sensitivity test, the patient's outcome with many risk factors, immunocompromised condition, unclear source of infection, aside from septic shock that led to the patient's death during treatment. Conclusion: Clinicians need to be aware of immunocompromised elderly patients and act quickly to help them. They also need to deal with the diagnostic difficulties of identifying definitive infectious sources, the high risk of death even with modern treatments, and the important role that underlying comorbidities play in prognosis. Clinical evidence shows that purulent pericarditis is still a serious condition that can have adverse outcomes, especially in older patients who already have a lot of health problems.